Integrating Cloud Computing for Improved Healthcare IT Infrastructure (Journal of the College of Basic Education, 2025)
Cloud computing is revolutionizing healthcare by enabling scalable, secure, and cost-efficient IT infrastructures that improve patient outcomes and organizational efficiency. This paper critically examines how cloud technologies can enhance healthcare IT systems through improved data accessibility, operational flexibility, and support for real-time clinical decision-making. Key concerns such as data privacy, security, and regulatory compliance are explored in depth. Through comprehensive literature review, international case studies including those from the U.S., UK, India, and Iraq and a proposed integration framework, the study offers strategic insights into implementing cloud computing in diverse healthcare contexts. The findings underscore the potential of cloud adoption to bridge digital divides, particularly in developing countries, while advancing global health objectives.